Penatalaksanaan Fisioterapi Pada Kasus Bronchitis Chronic Di BBKPM Surakarta - Indriyani, Indriyani (Research of Service Administration Health and Sains Healthys, 2020)
Background : Chronic bronchitis is inflammation of the bronchi of continuous and progressive improvement in productive cough and dyspnea that can not be attributed to specific causes that have a productive cough throughout the day for at least 3 consecutive months. Modality given in these conditions in the form of Infra Red, Chest Therapy and Nebulizer Purpose : Scientific Writing aims to determine the benefits, the cause, the cause and effect as well as the management and the influence of infra red, chest therapy and nebulizer in patients with chronic bronchitis and how the signs and symptoms of the disease. Methods :In the case studies, conducted by the physiotherapy management of infra-red method, chest therapy and nebulizer after therapy as much as 6x obtained results. Result : An increase in the thorax expansion during therapy to 1 (T1) the result is the axilla showed inspiration: 87 cm, 86 cm expiration by a margin of 1 cm, and at the end of therapy (T6) in the axilla is obtained inspiration: 90 cm, expiration: 87,4 cm by a margin of 2,6 cm. At proc. Xypoideus when therapy to 1 (T1) is obtained inspiration: 89 cm, 88 cm expiration by a margin of 1 cm, and at the end of therapy (T6) on proc. RESULTS inspiration Xypoideus 92 cm, 89,6 cm by a margin expiratory 2,4 cm. Their frequency decreased shortness of breath that at the time of treatment to 1 (T1) obtained the value of asphyxiation 4 (slightly heavy) and at the end of therapy to 6 showed breathlessness value of 0 (not at all feel shortness of breath). A decrease in chest pain during therapy to 1 (T1) is obtained by using the value of chest pain VAS (4.2) that at the end of therapy (T6) is obtained VAS value (2.3). Conclusions :Management of physiotherapy in the condition of Chronic Bronchitis with infra red modalities, chest therapy, and used Nebulizer shows the increase certainly better direction. Showed an increase in thoracic expansion, a decrease shortness of breath and chest pain decrease.